Prevalence of Radiographic and Symptomatic Hip Osteoarthritis in an Urban United States Community: The Framingham Osteoarthritis Study. Issue 11 (November 2014) - Kim, Chan; Linsenmeyer, Katherine D.; Vlad, Steven C.; Guermazi, Ali; Clancy, Mary M.; Niu, Jingbo; Felson, David T.
<x xml:space="preserve">Abstract</x> Objective The last prevalence survey encompassing urban populations was part of the First National Health and Nutrition Examination Survey, conducted in the 1970s. The aim of the present study was to perform a prevalence survey of hip osteoarthritis (OA) among individuals in the Framingham Study Community cohort. Methods Individuals ages 50 years and older living in Framingham, Massachusetts in 2002–2005 were recruited by random digit dialing, with selection made regardless of whether joint pain or arthritis were reported. Anteroposterior radiographs of the long limbs of the lower extremities, including the pelvis, were obtained with individuals placed in a standing position. The radiographs were read by two trained physicians for the presence of radiographic hip OA, with all possible cases of radiographic hip OA confirmed by an experienced musculoskeletal radiologist. Radiographic hip OA was defined as a Kellgren/Lawrence radiographic severity grade of ≥2. Using a homunculus in which the hip joint was depicted, participants were asked whether they had hip pain on most days. Those who responded "yes" were defined as having hip pain. Symptomatic hip OA was defined as radiographic OA with ipsilateral hip pain. We defined a person as having hip OA if at least one of the hip joints was affected. Results Of 978 subjects studied (mean age 63.5 years; 56% women), the age‐standardized prevalence of radiographic hip OA was 19.6% (95% confidence interval [95% CI] 16.7–23.0%) and the age‐standardized prevalence of symptomatic hip OA was 4.2% (95% CI 2.9–6.1%). Overall, men were observed to have a higher prevalence of radiographic hip OA (P < 0.0001) compared to women, but men did not have a higher prevalence of symptomatic hip OA compared to women (5.2% versus 3%; P = 0.08). Conclusion Hip OA is a common condition in middle‐aged and older individuals in urban and suburban areas of the US.